2017
DOI: 10.1159/000481416
|View full text |Cite|
|
Sign up to set email alerts
|

Prospective Comparison of Gd-EOB-DTPA-Enhanced MRI with Dynamic CT for Detecting Recurrence of HCC after Radiofrequency Ablation

Abstract: Background: We prospectively compared the efficacy of gadolinium-ethoxybenzyl-diethylenetriamine pentaacetic acid (Gd-EOB-DTPA)-enhanced magnetic resonance imaging (MRI) with that of dynamic multidetector computed tomography (MDCT) for detection of recurrent hypervascular hepatocellular carcinoma (HCC) after radiofrequency ablation (RFA). Methods: Institutional review board approval and written informed consent were obtained for this multicenter study. Ninety-seven HCC patients treated with curative RFA underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…However, after radical treatment, patients with early liver cancer have a high intrahepatic recurrence rate, and the survival rate is still not satisfactory [38]. This may be correlated to the failure to detect metastases before the first radical treatment [6]. The detection results of potentially suspicious small HCC lesions would affect the preoperative BCLC staging of some patients.…”
Section: Clinical Application For Treatment Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, after radical treatment, patients with early liver cancer have a high intrahepatic recurrence rate, and the survival rate is still not satisfactory [38]. This may be correlated to the failure to detect metastases before the first radical treatment [6]. The detection results of potentially suspicious small HCC lesions would affect the preoperative BCLC staging of some patients.…”
Section: Clinical Application For Treatment Programsmentioning
confidence: 99%
“…When the final diagnosis is made with typical symptoms, the stage of the disease is often advanced [3]. With the exception of some patients who received early diagnosis and prompt surgical resection or liver transplantation, the overall prognosis of HCC remains poor [4], with a median survival time of < year and a 5-year survival rate of < 10% [5], and a high recurrence rate [6]. HCC with a single tumor of ≤ 3.0 cm is usually referred to as small HCC [7].…”
Section: Introductionmentioning
confidence: 99%
“…Following the extensive application of multislice computed tomography (MSCT), CT evaluations of HPD have previously been reported ( 10 ). However, few MRI evaluations of HPD have been reported, which is likely due to the fact that the use of MRI in imaging for evaulating HPD was introduced after CT and MRI is not used as widely as CT in imaging of HPD ( 11 ). However, the features of HPD in MRI imaging have been described in the literature ( 1 ), and it has been reported that MRI imaging maybe used to indicate the characteristics of different hepatic diseases that cause HPD ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the AASLD 2018 practice guidance recommendations, the Liver Imaging Reporting and Data System (LI‐RADS) system was proposed as a radiological hallmark of observations associated with category codes . As a hepatocyte‐specific imaging modality, gadoxetic acid–enhanced MRI shows higher sensitivity for detecting premalignancies or hypervascular recurrences after thermal ablation compared with multiphase CT or MRI with the use of an extracellular contrast agent . According to most studies, current diagnostic algorithms are applicable for characterizing recurrence based on the assumption that the imaging patterns of recurrent HCCs would be the same as those of primary HCCs .…”
mentioning
confidence: 99%
“…As a hepatocyte‐specific imaging modality, gadoxetic acid–enhanced MRI shows higher sensitivity for detecting premalignancies or hypervascular recurrences after thermal ablation compared with multiphase CT or MRI with the use of an extracellular contrast agent . According to most studies, current diagnostic algorithms are applicable for characterizing recurrence based on the assumption that the imaging patterns of recurrent HCCs would be the same as those of primary HCCs . Moreover, recurrent HCCs frequently show atypical enhancement patterns, which may lead to additional false‐negative results if stringent diagnostic criteria must be met.…”
mentioning
confidence: 99%